Fiscal and Regulatory Instruments for Clean Technology Development in the European Union - Antoine Dechezleprêtre; David Popp (Center for Economic Studies and ifo Institute (CESifo), 2015)
This policy note investigates whether the current level of public support to environment-friendly technologies is sufficient to allow European countries to respond to the multiple challenges posed by climate change and other environmental concerns. We first lay out the justifications for government support to clean R&D activity at the various stages of technology development, discussing particular features of clean technologies that justify policy intervention. We present empirical evidence for the impact of various policies on the development of clean technologies and use this to identify what the appropriate policy mix should look like. We present an overview of policies currently in place to support the development of clean technologies across Europe and compare the current policy landscape to the appropriate policy portfolio. This comparison allows us to provide some practical steps for reform.
Keywords: O38; Q42; Q55; 330; climate change; renewable energy; environmental policy; innovation; diffusion